1982
DOI: 10.1002/tera.1420260304
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effects of lithium in mice

Abstract: The question of the teratogenicity of lithium carbonate was tested in two inbred strains of mice that are susceptible to teratogens. Strains 129 and A/J mice were treated with varying dosages of lithium carbonate on day 8, 9, or 10, and strain A/J mice were sequentially treated on days 11, 12, and 13 of gestation. Another group of mice of strain 129 were given lithium carbonate in drinking water throughout pregnancy. Levels of lithium were determined in mouse serum (and in brain) of mothers and their offspring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Using rodent or avian models, we targeted the embryo during the primitive-streak stage. Previous studies have exposed the embryo to Li or HCy, but only after a tubular cardiac structure was already present at E8.0, or later (Nelson et al, 1955;Rosenquist et al, 1996;Smithberg and Dixit, 1982). This communication compares our HCy exposure studies during gastrulation with the cardiac defects induced by Li and analyzes the common FA rescue of the defects.…”
Section: Discussionmentioning
confidence: 88%
“…Using rodent or avian models, we targeted the embryo during the primitive-streak stage. Previous studies have exposed the embryo to Li or HCy, but only after a tubular cardiac structure was already present at E8.0, or later (Nelson et al, 1955;Rosenquist et al, 1996;Smithberg and Dixit, 1982). This communication compares our HCy exposure studies during gastrulation with the cardiac defects induced by Li and analyzes the common FA rescue of the defects.…”
Section: Discussionmentioning
confidence: 88%
“…We found that not only serious abnormalities such as exencephaly significantly were over-represented in dead fetuses (Shenefelt, 1972) but also minor anomalies with only a local effect on the fetus such as a cleft lip ( Fig. 2; Walker and Crain, 1959;Smithberg and Dixit, 1982;Juriloff and Harris, 1985;Nakane and Kameyama, 1983) and a short tail (Dostal and Jelinek, 1979). The presence of an anomaly with a small local effect cannot increase mortality by itself (see control experiment in Fig.…”
Section: Differential Mortalitymentioning
confidence: 79%
“…These differences could be attributable, in part, to a difference in kinetics of LiCl and TCDD. The elimination half-life of LiCl and TCDD are about 4 hr (Smithberg and Dixit, 1982) and 10-24 d (Birnbaum, 1986), respectively. We administered LiCl daily to keep its effects, which should have resulted in the oscillation of serum lithium level with a high level immediately after injection and a low level before the next injection.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, lithium is contraindicated for use in the pregnant and lactating women because teratogenicity, such as fused ribs and defective vertebra, was reported in mouse (Smithberg and Dixit, 1982) and rat (Marathe and Thomas, 1986), and is suspected in humans from retrospective studies (Yacobi and Ornoy, 2008). However, the prospective studies of lithium treated women in pregnanand Ornoy, 2008).…”
Section: Discussionmentioning
confidence: 99%